Transformasi Genetik Pisang Ambon dengan Gen Kitinase dari Padi - Ragapadmi Purnamaningsih; Deden Sukmadjaja (Jurnal AgroBiogen, 2012)
One of the main constrains on theproductivity and quality enhancement of banana is wiltdiseases caused by Fusarium oxysporum (Foc). Productiondecrease by wilt disease was 63.33%. Therefore, an effort toobtain the banana new variety which is tolerant to fusariumwas absolutely necessary to be done. Genetic engineeringcan be used in new variety improvement, especially forproduction of pest and disease tolerant varieties.Transformation of banana with chi gene which expressedchitinase enzyme have been used in obtaining the plantresistant to Foc. The goals of the research were to obtain:determine lowest higromisin consentration inhibited nodulgrowth by tested four consentration of higromisin,determine optimum cocultivation time by tested three timescocultivation, tested asetosiringone added on two timescocultivation, and gen chi introduction at bananatransforman shoots with PCR. The explants used werenodule induced from pseudostem of banana cv. Ambonkuning. Genetic transformation done by sowing the explantsin bacterial suspension 0, 15, 30, and 45 minutes.The effectof asetosiringone (0 and 100 mg/l) on cocultivation mediumwas observed. The research results showed that the lowesthigromisin concentration inhibited nodule growth was 25mg/l for 5 weeks and the best time for inoculation of nodulewere 30 minute. Asetosiringone added on bacterialsuspension did not increase transformation efficiency.Chitinase gene transformation using Agrobacteriumtumefaciens on banana nodules produced 25 noduly ines ofputative transformant on selection media and 34 plantstransforman identification by PCR.